Ultrastructure of the male accessory glands of sesarmid crab, Parasesarma plicatum (Latreille, 1803). Issue 2 (June 2017) - Ganapiriya, Viswambaran; Shyla Suganthi, Arundathi; Maharajan, Athisuyambulingam
Abstract: The structure of accessory glands (AGs) in the male sesarmid crab, Parasesarma plicatum, is described by light and transmission electron microscopy. Adult males of carapace of width 1.6–2.2 cm were collected from along the estuarine regions of Kanyakumari District, India. Posteriorly, the male reproductive system receives several sac-like structures, referred to as AGs. Histologically, the AG is internally lined by cuboidal epithelium and the lumen encloses eosinophilic vesicular secretions, apparently glycopreoteinaceous in nature. Ultrastructurally, the epithelium shows the signs of typical infrastructure for synthetic activity, as demonstrated by the prolific presence of rough endoplasmic reticulum, free ribosomes, and Golgi complex. The cytoplasm is manifested with electron-dense, electron-lucent, and medium-density secretory vesicles, and the mode of release into the lumen is both merocrine and apocrine. Within the lumen, these secretory vesicles coalesce and aggregate into large heterogeneous masses of varying sizes, which may play an important role post-copulation within the female duct.